GLOBAL EXISTENCE AND EXPONENTIAL DECAY TO THE WAVE EQUATION WITH LOCALIZED FRICTIONAL DAMPING - Santiago Ayala, Yolanda Silvia (2002)
In this paper we show the global existence and the exponencial decay of solutions of the one-dimensional wave equation with localized frictional damping.